UJI DAYA HAMBAT EKSTRAK DAUN SIRSAK (Annona muricata L) TERHADAP BAKTERI Escherichia Coli DAN Staphylococcus Aureus DENGAN METODE DIFUSI CAKRAM - Marantika Komalasari; Radho Alkausar; Agustina Retnaningsih (Jurnal Analis Farmasi, 2021)
This study aims to determine the antibacterial inhibition of soursop leaf extract against Escherichia coli and Staphylococcus aureus bacteria. Antibacterial test against Escherichia coli and Staphylococcus aureus bacteria using disc diffusion method. The concentration of soursop leaf extract used was 25%, 50%, 75% and 100% with Tetracycline antibiotics as a positive control.  The results of this study showed soursop leaf extract against Escherichia coli bacteria at a concentration of 25%, namely 0.00 mm, at a concentration of 50%, namely 8.30 mm, at a concentration of 75%, namely 8.80 mm, and at a concentration of 100%, namely 9.90  mm.  While soursop leaf extract against Staphylococcus aureus bacteria at concentrations of 25%, 50%, 75% and 100% did not get inhibition zones in each repetition. The results of testing the inhibitory power of soursop leaf extract were more effective on Escherichia coli bacteria which are gram- negative bacteria.